Mejora escolar, liderazgo y reforma sistémica: una retrospectiva (School improvement, leadership and systemic reform: a retrospective) - Hopkins, David (Revista Eletrônica de Educação, 2019)
During the last four decades, the bases of research on effectiveness and school improvement have been gaining recognition at the international level. Both theoretically and empirically, they have matured through a wide range of well-documented and innovative projects in several countries. In general, these works focus on the successes and failures related to the different initiatives aimed at making schools more effective learning environments for all students. In the following article, the British researcher David Hopkins delivers evidence of the results of these efforts, summarized in five phases of development. He concludes by re?ecting on how these phases evolve and overlap, examines some myths that hinder school and systemic improvement and proposes some guidelines for future research. Resumo Durante as últimas quatro décadas, as bases da pesquisa sobre eficácia e melhora escolar vêm ganhando reconhecimento no plano internacional. Teórica e empiricamente, eles amadureceram através de uma ampla gama de projetos bem documentados e inovadores em vários países. Em geral, esses trabalhos enfocam os sucessos e fracassos relacionados às diferentes iniciativas que visam tornar as escolas ambientes de aprendizagem mais eficazes para todos os alunos. No seguinte artigo, o pesquisador britânico David Hopkins apresenta evidências dos resultados desses esforços, sintetizado em cinco fases de desenvolvimento. Ele conclui re?etindo sobre como essas fases evoluem e se sobrepõem, examina alguns mitos que impedem a melhora sistêmica escolar e propõe algumas diretrizes para pesquisas futuras. Resumen Durante las cuatro últimas décadas, las bases de la investigación sobre la efectividad y la mejora escolar han ido cobrando reconocimiento en el plano internacional. Tanto a nivel teórico como empírico, han madurado a través de una amplia gama de bien documentados e innovadores proyectos en varios países. Por lo general, estos trabajos se centran en los éxitos y fracasos relativos a las diferentes iniciativas tendientes a que las escuelas se transformen en entornos de aprendizaje más efectivos para todos los estudiantes. En el siguiente capítulo, el investigador británico David Hopkins entrega evidencia de los resultados de dichos esfuerzos, resumida en cinco fases de desarrollo. Concluye re?exionando sobre cómo dichas fases evolucionan y se superponen, examina algunos mitos que obstaculizan el mejoramiento escolar y sistémico y propone algunas orientaciones para futuras investigaciones. Keywords: School improvement, Leadership, Systemic reform, Learning. Palavras-chave: Melhora escolar, Liderança, Reforma Sistêmica, Aprendizagem. Palabras claves: Mejora escolar, Liderazgo, Reforma sistémica, Aprendizaje. References ALSBURY, T. L.The future of school board governance: Relevancy and revelation. Blue Ridge Summit, PA: Rowman & Littlefield Education, 2008. ANDERSON, S. (ed.) School improvement in the developing world: case studies of the Agha Khan Foundation Projects. Lisse, Holanda: Swets and Zeitlinger Publishers, 2002. AVALOS, B. School Improvement in Latin America: innovations over 25 years (1980-2006). In: T. TOWNSEND (ed.) International handbook on school effectiveness and improvement. Dordrecht, NL: Springer, 2007, pp. /xx-YYY. BARBER, M. Instruction to deliver: Tony Blair, the public services and the challenge of delivery. Londres: Politico's, 2007. BARBER, M. From system effectiveness to system improvement. In: HARGREAVES, A. & FULLAN, M. (Eds.). Change wars. Bloomington, IN: Solution Tree, 2009. BARBER, M.; FULLAN, M.; MACKAY, A.; ZBAR, V. Building excellent education systems: from conception to implementation at scale. Melbourne: Centre for Strategic Education Seminar Series Paper No. 189, noviembre 2009. BERENDS, M.; BODILLY, S. J.; KIRBY, S. N. Facing the challenges of whole-school reform: new American Schools after a decade. Santa Mónica, CA: RAND, 2002. BERMAN, P.; MCLAUGHLIN, M. Federal programs supporting educational change. Vol. VIII, Implementing and sustaining innovations. Santa Mónica, CA: Rand, 1978. BISHOP, R.; O’SULLIVAN, D.; BERRYMAN, M. Scaling up education reform: addressing the politics of disparity. Wellington: NZCER Press, 2010. BIRDSALL, N. The world is not flat: inequality and injustice in our global economy. WIDER Annual Lecture No. 9. Helsinki, Finlandia: UNU-Wider, 2006. BITAR, S. Why and How Latin America Should Think About the Future. Washington, DC: Inter-American Dialogue, 2013. BORMAN, G.D.; HEWES, G.M.; OVERMAN, L.T.; BROWN, S. Comprehensive School Reform and achievement: A meta-analysis. Review of Educational Research, 73, 2003, pp. 125-230. BRANDSFORD, J. D.; BROWN, A. L.; COCKING, R. R. How People Learn: Brain, Mind, Experience, and School. Washington, DC: National Academy Press, 1999. CALDWELL, B.J.; SPINKS, J.M. The Self-managing School. Lewes: Falmer Press, 1988. CAMARA, G. Q and A with Gabriel Camara. Lead the Change Series. Issue No. 11, 2011. November. recuperado de : http://www.aera.net/educational_change_sig.htm. CLIFT, P., NUTTALL, D. AND MCCORMICK, R. Studies in School Self-Evaluation. Lewes: Falmer Press, 1987. CHAPMAN, C.; LINDSAY, G.; MUIJS, D.; HARRIS, A.; ARWECK, E.; GOODALL, A. Governance, Leadership and Management in Federations of Schools, School Effectiveness and School Improvement, Vol. 22, No. 1, 2010, pp. 53-75. CHILDRESS, S. Six lessons for pursuing excellence and equity at scale, Phi Delta Kappan,10(3), 2009, pp. 13–18. COLBERT, V. Q and A with Vicky Colbert. Lead the Change Series. Issue No. 29, August, 2013. Recuperado de: http://www.aera.net/educational_change_sig.htm. COMER, J. For Children’s Sake: Comer School Development Program, discussion leaders guide, New Haven, CT: Yale Child Study Center, 1992. COMER, J. Leave no child behind. New Haven, CT: Yale University Press, 2005. CRANDALL, D.P.; LOUCKS, S.F. A roadmap for school improvement: executive summary of the study of dissemination efforts supporting school improvement. Andover, MA: The Network, 1983. DALIN, P. Case Studies of Educational Innovation’, Vol IV. In: Strategies for Educational Innovation, París: CERI/OECD, 1973. DATNOW, A.; LASKY, S.; STRINGFIELD, S.; TEDDLIE, C. Systemic integration for effective reform in racially and linguistically diverse contexts. Nueva York: Cambridge University Press, 2006. DAY, C.; SAMMONS, P.; LEITHWOOD, K.; HOPKINS, D.; QING GU; BROWN, C. Ten strong claims about successful school leadership. Nottingham: NCSL, 2010. DAY, C.; SAMMONS, P.; HOPKINS, D.; HARRIS, A.; LEITHWOOD, K.; QING GU; BROWN, E.; AHTARIDOU, E. Successful school leadership: linking with learning and achievement. Maidenhead, Berkshire: Open University Press, 2011. DEPARTAMENTO DE EDUCACIÓN de Estados Unidos. A Nation At Risk, 1983. DESIMONE, L. How can comprehensive school reform models be successfully implemented? Review of Educational Research, 72(3), 2002, pp. 433-479. DWYER, D. The search for instructional leadership routines and subtleties in the principal’s role, Educational Leadership, 41, 1984, pp. 32-37; EARL, L.; TORRANCE, N.; SUTHERLAND, S.; FULLAN, M.; ALI, A.S. Manitoba school improvement program final evaluation report. OISE/UT. Toronto: Walter and Duncan Gordon Foundation, 2003. Disponible en www.msip.ca EARL, L.; KATZ, S. Learning from the Networked Learning Communities: Research Report. Nottingham: NCSL, 2005. EDMONDS, R. Effective schools for the urban poor. Educational Leadership, 37 (1), 1979, pp. 15-27. ELLIOTT, J. Action Research for Educational Change. Milton Keynes: Open University Press, 1991. ELMORE, R. F. School Reform from the Inside Out. Cambridge, MA: Harvard Education Press, 2004. FINN, C.; MANNO, B.; VANOUREK, G. Charter Schools in Action: Renewing Public Education, Princeton, Nueva Jersey: Princeton University Press, 2001. FLEISCH, B. A history of the school effectiveness and improvement movements in Africa.’ In: T. TOWNSEND (ed.). International Handbook on School Effectiveness and Improvement. Dordrecht, NL: Springer, 2007. FLESSA, J.; BRAMWELL, D.; FERNÁNDEZ, M.; WEINSTEIN, J. School Leadership in Latin America 2000- 2016. Educational Management and Leadership, XX (X), 2017, pp. 1-25. FULLAN, M.G.; MILES, M.B.; TAYLOR, G. Organization development in schools: the state of the art. Review of Educational Research, 50 (1), 1980, pp. 121-184. FULLAN, M. The moral imperative of school leadership. Londres: Corwin Press, 2003. FULLAN, M. Leadership and sustainability. System leaders in action. Londres: SAGE, 2004. FULLAN, M. System thinkers in action: moving beyond the standards plateau. Londres/Nottingham: DfES Innovation Unit/NCSL, 2004. FULLAN, M. The new meaning of educational change. (4th Ed.). Nueva York: Teachers College Press, 2007. FULLAN, M. Large scale reform comes of age. Journal of Educational Change, 10(2), 2009, pp. 101-113. FULLAN, M. All systems go. Thousand Oaks, CA: Corwin, 2010. GENERAL ACCOUNTING OFFICE. Effective schools programs: Their extent and characteristics. Gaithersberg, MD: Author, 1989. GOOD, T.L.; BROPHY, J.E. Looking In Classrooms. (8th ed.). Nueva York: Harper and Row, 2008. GLICKMAN, C. Renewing America’s schools: A guide for school-based action. San Francisco: Jossey-Bass, 1993. GRAY, J.; HOPKINS, D.; REYNOLDS, D.; WILCOX, B.; FARRELL, S.; JESSON, D. Improving schools: performance and potential. Buckingham: Open University Press, 1999. HALLINGER, P.; MURPHY, J. Assessing the instructional management behaviour of principals. Elementary School Journal. 85, 1985, pp.217-247. HALLINGER, P. Leadership for learning: what we have learned from 30 years of empirical research. Centre for Strategic Education Seminar Series Paper No. 196, julio 2010. HARGREAVES, A.; HALÁSZ, G.; PONT, B. School leadership for systemic improvement in Finland. París: Organization for Economic Cooperation and Development, 2007. HARGREAVES, A.; SHIRLEY, D. The fourth way. Thousands Oakes, CA: Corwin, 2009. HARGREAVES, A.; LIEBERMAN, A.; FULLAN, M.; HOPKINS, D. Second international handbook of educational change. Volumes 1 and 2. Springer Dordecht: Heidelberg, London, Nueva York, 2010. HARGREAVES, D. H.; HOPKINS, D. The empowered school: the management and practice of development planning. Londres: Cassell, 1991. HARRIS, A. (ed.) Distributed leadership. Dordrecht, NL: Springer, 2010. HARRIS, A.; YOUNG, J. Comparing school improvement programmes in the United Kingdom and Canada: lessons learned. School Leadership and Management, 20(1), 2000, pp. 31-43. HARRIS, A.; LAMBERT, L. Building leadership capacity for school improvement. Milton Keynes: Open University Press, 2003. HARRIS, A.; CHRISPEELS J. (eds.) International perspectives on school improvement. Londres, Routledge Falmer, 2008. HARRIS, A.; JONES, M. Professional learning communities and system improvement. Improving Schools, 13(2), 2010, pp. 172-181. HARRIS, A. JONES, M. Leading educational change and improvement at scale: some inconvenient truths about system performance. International Journal of Leadership in Education, 2017. DOI: 10.1080/13603124.2016.1274786. HIGHAM, R.; HOPKINS, D.; MATTHEWS, P. System leadership in practice. Maidenhead, Berkshire: Open University Press, 2009. HOPKINS, D. Change and the organisational character of teacher education. Studies in Higher Education, 9(1), 1984, pp. 37-45. HOPKINS, D. (Ed.). Improving the quality of schooling. Lewes: Falmer, 1987. HOPKINS, D. Institutional self-evaluation and renewal. In: T. HUSEN AND N. POSTLETHWAITE (eds.). The international encyclopaedia of education. Nueva York: Pergamon, 1994. HOPKINS, D. School improvement for real. Londres: Routledge/Falmer, 2001. HOPKINS, D. Improving the quality of education for all: a handbook of staff development activities. (2a ed.). Londres: David Fulton Publishers, 2002. HOPKINS, D. Every school a great school. Maidenhead, Berkshire: Open University Press, 2007. HOPKINS, D. (ed.) Transformation and innovation: system leaders in the global age. Londres: Specialist Schools and Academies Trust, 2007. HOPKINS, D. Hacia una buena escuela: experiencias y lecciones. Santiago, Chile: Fundación Chile, 2008. HOPKINS, D. Mi escuela, una gran escuela. Santiago: Lom Ediciones / iNet, 2009. HOPKINS, D. Powerful learning: taking educational reform to scale, Paper No. 20, March 2011, Melbourne, Victoria: State Government of Victoria, Department of Education and Early Childhood Education, 2011. HOPKINS, D. Exploding the myths of school reform. Melbourne, Australia: ACER Press, and Maidenhead, Berkshire: Open University Press / McGraw-Hill Education, 2013. HOPKINS, D.; AINSCOW, M.; WEST, M. School improvement in an era of change. Londres: Cassell, 1994. HOPKINS, D.; HARRIS, A.; JACKSON, D. Understanding the school’s capacity for development: growth states and strategies. School Leadership and Management, 17(3), 1997, pp. 401-411. HOPKINS, D.; HARRIS, A.; SINGLETON, C.; WATTS, R. Creating the conditions for teaching and learning. A handbook of staff development activities. Londres: David Fulton Publishers, 2000. HOPKINS, D.; REYNOLDS, D. (2001). The past, present, and future of school improvement: towards the third age. British Educational Research Journal, vol. 27, n4, 2001, pp. 459-75. HOPKINS, D.; MACKAY, T. Leadership for transforming learning. Think tank report prepared for the National College of School Leadership. Nottingham: NCSL, 2001. HOPKINS, D.; MUNRO, J.; CRAIG, W. Powerful learning: a strategy for systemic educational improvement. Melbourne, Australia: ACER Publishers, 2011. HOPKINS, D.; CRAIG, W. Leadership for powerful learning. Melbourne: McREL International / Cambridge: Pearson Publishing, 2015/17. JACKSON, D.; TEMPERLEY, J. From professional learning community to networked learning community. In: L. STOLL AND K. S. LOUIS (eds.). Professional learning communities: divergence, depth and dilemmas. Maidenhead: Open University Press, 2007. JOYCE, B. R.; SHOWERS, B. Student achievement through staff development. (2nd ed.). New York: Longman, 1995. JOYCE, B.R.; WEIL, M.; CALHOUN, E. F. Models of teaching. (9th ed.). Boston: Pearson, 2015. JOYCE, B. R.; CALHOUN, E. F.; HOPKINS, D. Models of learning – tools for teaching. (Third Edition), Maidenhead, Berks, Reino Unido: Open University Press, 2009. JOYCE, B. R.; CALHOUN, E. F. Models of professional development: a celebration of educators. Thousand Oaks, California: Corwin Press, 2010. KASER, L.; HALBERT, J. From sorting to learning: developing deep learning in Canadian schools. Education Canada, 48 (5), 2008, pp. 56-59. KATZ, S.; EARL, L. Learning about networked learning communities. School Effectiveness and School Improvement, 21(1), 2010, pp. 27-52. LEITHWOOD, K. Characteristics of school districts that are exceptionally effective in closing the achievement gap. Leadership and Policy in Schools, 9, (3), July – September, 2010, pp. 245-291. LEITHWOOD, K.; JANTZI, D.; MASCALL, B. Large scale reform: what works? Unpublished manuscript. Toronto: Ontario Institute for Studies in Education, University of Toronto, 1999. LEITHWOOD, K.; RIEHL, C. What do we know about successful school leadership. University Council on Education Administration, Task Force on Research and Educational Leadership, 1999 Consultado el 10 de noviembre de 2004 en: http://www.cepa.gse.rutgers.edu/whatweknow.pdf Leithwood Wallace 04 LEITHWOOD, K.; DAY, C.; SAMMONS, P.; HOPKINS, D.; HARRIS, A. Seven strong claims about successful school leadership. Nottingham: NCSL, 2007. LEWIN, K. Group decisions and social change. In: T.M. NEWCOMB AND E.L. HARTLEY (eds.). Readings in social psychology. New York: Henry Holt, 1947. LOCKHEED, M.; PROKIC-BRUER, T.; SHADROVA, A. The experience of middle-income countries participating in PISA 2000-2015. París: PISA, World Bank, Washington, D.C.: OECD Publishing, 2015. LOUIS, K.S.; LEITHWOOD, K.; WAHLSTROM, K. L.; ANDERSON, S. E. Investigating the links to improved student learning. Final report of research findings. Minneapolis: University of Minnesota and Ontario Institute for Studies in Education/University of Toronto, 2010. LUCAS, B.; CLAXTON, G. New kinds of smart: how the science of learnable intelligence is changing education. Maidenhead: Open University Press, 2010. MACBEATH, J.; MORTIMORE, P. Improving school effectiveness. Buckingham: Open University Press, 2001. MCLAUGHLIN, M. The rand change agent study revisited: macro perspectives and micro realities. Educational Researcher, 19(9), 1990, pp. 11-16. MCKINSEY. How the world’s best performing school systems come out on top. Londres: McKinsey, 2007. MCKINSEY. How the world’s most improved school systems keep getting better. Londres: McKinsey, 2010. MILES, M.B. Some properties of schools as social systems. In: G. WATSON (ed.) Change in schools systems. Washington DC: National Training Laboratories, 1967. MILES M.B. Planned change and organisational health. In: J.V. BALDRIGE & T. DEAL (eds.). Managing change in educational organisations. Berkeley: McCutchen, 1975. MUIJS, D. A fourth phase of school improvement? Introduction to the special issue on networking and collaboration for school improvement. School Effectiveness and School Improvement, 21(1), 2010, pp. 1-4. MURPHY, J. Restructuring schools: capturing and assessing the phenomena. New York: Teachers College Press, 1991. NUNNERY, J. A. Reform ideology and the locus of development problem in educational restructuring. Education and Urban Society, 30(3), 1998, pp. 277-295. OECD. PONT, B.; NUSCHE, D.; MOORMAN, H. Improving school leadership: policy and practice. París: OECD, 2008. OECD. PONT, B.; MOORMAN, H.; HOPKINS, D. Improving school leadership: case studies on system leadership policy and practice. París: OECD, 2008. OECD. Nature of learning project. París: OECD, 2010. OECD. Education at a glance 2016: OECD Indicators. París: OECD Publishing, 2016. O’SHAUGHNESSY, J. Competition meets collaboration: helping school chains address England’s long tail of educational failure.Londres: Policy Exchange, 2012. POWELL, J. The new Machiavelli: how to wield power in the modern world. London: Vintage Books, 2010. PURKEY, S.C.; SMITH, M.S. Effective schools - A review. The Elementary School Journal, 83, 1983, pp. 427-452. PURKEY, S.C.; SMITH, M.S. School reform: the district policy implications of the effective schools literature. The Elementary School Journal, 85(3), 1985, pp. 353-389. REYNOLDS, D.; CREEMERS, B.; STRINGFIELD, S.; TEDDLIE, C.; SCHAFFER, E. World class schools: International perspectives on school effectiveness. New York: Routledge/Falmer, 2002. REYNOLDS, D.; SAMMONS, P.; STOLL, L.; BARBER, M.; HILLMAN, J. School effectiveness and school improvement in the United Kingdom, School Effectiveness and School Improvement, 7(2), 1996, pp. 133-158. REYNOLDS, D.; STRINGFIELD, S.; SCHAFFER, E. The high reliability schools project: some preliminary results and analyses. In: J. CHRISPEELS & A. HARRIS (Eds.). School improvement: international perspectives. Londres: Routledge, 2006, pp. 56-76. ROBINSON, V.; HOHEPA, M.; LLOYD, C. School leadership and student outcomes: identifying what works and why. Best evidence synthesis programme. Wellington: Ministerio de Educación de Nueva Zelanda, 2009. RUDDUCK, J.; HOPKINS, D. Research as a basis for teaching. London: Heinemann, 1985. SARASON, S. The culture of the school and the problem of change. (2a. edition). Boston: Allyn and Bacon, 1982. SCHILDKAMP, K.; VISSCHER, A.; LUYTEN, H. The effects of the use of a school self-evaluation instrument. School Effectiveness and School Improvement, 20 (1), 2009, pp. 69-88. SCHMUCK, R.A. Characteristics of the autonomous school. In: D. HOPKINS, & M. WIDEEN (eds.) Alternative perspectives on school improvement. London: Falmer, 1984. SCHMUCK, R.A.; MILES, M. (eds.). Organizational development in schools. Palo Alto, CA: National Press Books, 1971. SCHMUCK, R.A.; RUNKEL, P. The handbook of organizational development in schools. (3rd. ed.). Palo Alto, CA: Mayfield, 1985. SIZER, T.R. Diverse practice, shared ides. The essential school. In: H. WALBERG AND J. LANE (eds.). Organizing for learning: towards the twenty first century. Reston, VA: NASSP, 1989. SLAVIN, R.E. Education for all. Lisse, Holanda: Swets and Zertlinger, 1996. SLAVIN, R.E.; MADDEN, N. Two million children: success for all. Thousand Oaks: Sage, 2010. STENHOUSE, L. An introduction to curriculum research and development. Londres: Heinemann, 1975. STOLL, L. Extending the learning conversation: reflections on the second year of the ealing professional learning community. Londres: Ealing County Council and Creating Capacity for Learning, 2010. STOLL, L. Capacity building for school improvement or creating capacity for learning? A changing landscape. Journal of Educational Change, 10(2), 2009, pp. 115-127. STOLL, L.; FINK, D. Changing our schools: linking school effectiveness and school improvement. Buckingham: Open University Press, 1996. STOLL, L.; FINK, D. The cruising school: the unidentified ineffective school. In: L. STOLL AND K. MYERS (eds.). No quick fixes. Perspectives on schools in difficulty. Londres: Falmer Press, 1998. STOLL, L.; FINK, D.; EARL, E. It’s about learning (and it’s about time). Londres: Routledge/Falmer, 2003. STOLL, L.; LOUIS, K.S. Professional learning communities: divergence, depth and dilemmas. Maidenhead: Open University Press, 2007. STRINGFIELD, S.; REYNOLDS, D.; SCHAFFER, E. Improving secondary students' academic achievement through a focus on reform reliability: 4- and 9-year findings from the High Reliability Schools project. School Effectiveness and School Improvement, 19(4), 2008, pp. 409-428. STRINGFIELD, S.; REYNOLDS, D.; SCHAFFER, E. Toward high reliability, high quality public schools. Invited paper presented at the Best in the World Education Consortium. Denver: McREL, October, 2010. STRINGFIELD, S.; ROSS, S.; SMITH, L. (Eds.). Bold plans for school restructuring: the New American Schools designs. Mahwah, NJ: Lawrence Erlbaum Associates, 1996. STRINGFIELD, S.; YAKIMOWSKI, M. The promise, progress, problems, and paradoxes of three phases of accountability: a longitudinal case study of the Baltimore City Public Schools. American Educational Research Journal, 42(1), 2005, pp. 43-76. STRINGFIELD, S.; TEDDLIE, C. School effectiveness research, 19322008, including a call for future research. In: C. DAY (Ed.). International handbook on teacher and school development. Londres: Routledge/Falmer, en imprenta. TEDDLIE, C.; REYNOLDS, D. The international handbook of school effectiveness research. Londres: Falmer, 2000. TOWNSEND, T. (ed.). International handbook on school effectiveness and improvement. Dordrecht, NL: Springer, 2007. UNESCO. Overview of the 20 years of the major project of education in Latin America and the Caribbean. Santiago, Chile: UNESCO, 2001. VAN VELZEN, W. et al. Making school improvement work. Lovaina, Bélgica: ACCO, 1985. VERHAEGHE, G.; VANHOOF, J.; VALCKE, M.; VAN PETEGEM, P. Using school performance feedback: perceptions of primary school principals. School Effectiveness and School Improvement, 21 (2), 2010, pp. 167-188. VESCIO, V.; ROSS, D.; ADAMS, A. A review of research on the impact of professional learning communities on teaching practice and student learning. Teaching and Teacher Education, 24(1), 2008, pp. 80-91. VINOVSKIS, M. A. An analysis of the concept and uses of systemic educational reform. American Educational Research Journal, 33 (1), 1996, pp. 58-85. WATKINS, C. Learning, performance and improvement, research matters series no 34. Institute of Education, Londres: International Network for School Improvement, 2010. WEICK, K.E. Educational organizations as loosely coupled systems. Administrative Science Quarterly, 21, 1976, pp. 1-19. WEINSTEIN, J. The Latin American school and the challenge of developing fraternity. European Journal of Education, 50, 2, 2015, pp.131-33. WHAT WORKS CLEARINGHOUSE Intervention report: Reading recovery. U.S. Department of Education, Institute of Education Sciences, 2008. WHELAN, F. Lessons learned: how good policies produce better schools. Londres: Fenton Whelan (autoedición), 2009.